Adjusting the Beam-line Method for Positive-moment Yielding - Carskaddan, Phillip S.; Haaijer, Geerhard; Grubb, Michael A. (Engineering Journal, 1984)
The beam-line method is a convenient tool for the analysis of nonlinear building connections and inelastic rotations over the interior supports of highway bridge girders. However, the method presently presumes that a bending member remains elastic in positive bending. While this presumption may be acceptable at low load levels, residual stresses in rolled beams and welded girders combined with applied stresses are known to create inelastic behavior at moderate load levels and above. The purpose of this paper is to demonstrate how positive moment yielding may be accounted for in the beam-line method. As a result, the method may then be applied throughout the elastic range, the inelastic range and up to mechanism formation. An example problem will illustrate the adjusted method, and then some potential applications will be discussed.